Community Policing and Union Parishad: Shared Obligation in Restoration of Social Peace - Bashir Ahmed Mohammad Tarikul Islam (KILA Journal of Local Governance, 2014)
The paper intends to substantiate the nexus between community policing and Union Parishad for safeguard of social peace and stability in Bangladesh. Community policing is a relatively new but innovative concept in Bangladesh. In a nutshell, movement of community policing does not get pleasant appearance across the level and leftovers less effective , to some extent although it is perceived as a potential force to be flourished as an effective force to resolve community level problems and promote social justice. Collaborative effort between the community police and Union Parishad have essence to identify problems of crime and disorder as this innovative approach involves all elements of the community in the search for solutions to these problems. The paper is ended up with a variety of recommendations to expand the concept of community policing across level so as to ensure a society from criminality, volatility and discord.